Free radical scavenging activity of Lepidium Sativum seed extract in HFD/STZ induced diabetes. - S.S. DESAI,; M.V. WALVEKAR,; S.P. KHAIRMODE, (International Journal of Pharma and Bio Sciences, 2018)
Oxidative stress is the major cause of diabetes and its associated complications. The present study aims to evaluate the antioxidative potential of Lepidium sativum seed extract (LSE) on streptozotocin induced diabetic mice.Lepidium sativum seeds have been used to treat a variety of human aliments like bronchial asthma, local and rheumatic pain and diabetes due to presence of large number of alkaloids like lepidin and semilepidine, so to study its free radical scavenging activity we have selected these seeds. Adult albino male mice (Mus musculus L.) were divided into three groups viz. i) control group ii) diabetic group iii) recovery group. Diabetes was induced in mice by feeding with high fat diet (two weeks) followed by intraperitoneal injection of streptozotocin (STZ) (40 mg/kg body weight). The diabetic mice were administered orally with LSE (200 mg/kg body weight) for 28 days. After the completion of treatment ,liver and pancreas were removed and used for the estimation of oxidative stress parameters namely superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPx). The results showed that the level of all three antioxidative enzymes i.e. SOD, CAT and GPx werereduced in diabetic group as compared to control group but after the treatment of LSE ,significant rise in antioxidative enzymes in recovery group was observed. These finding suggests that LSE had increased the antioxidant enzymes by scavenging free radicals which significantly manage diabetes and its associated complications.